2013 IEEE 20th International Conference on Electronics, Circuits, and Systems (ICECS) 2013
DOI: 10.1109/icecs.2013.6815358
|View full text |Cite
|
Sign up to set email alerts
|

The revolution of glucose monitoring methods and systems: A survey

Abstract: Diabetes is characterized by high glucose levels in the blood that result from defects in insulin secretion, or its action, or both, being considered as one of the major contributors of precipitate infirmity and death in non-contagious diseases. Glucose meter is the prevailing technique to determine the glucose level, a technique involving chemical analysis of a sample of the diabetic blood obtained by pricking a finger. Yet, due to the many demerits of the glucose meter, including the pain and the direct cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For portable setup, several calibration techniques have been explored and implemented [55]. A number of deliberate attempts have been made to develop the self-monitoring system [56].…”
Section: Non-invasive Methodsmentioning
confidence: 99%
“…For portable setup, several calibration techniques have been explored and implemented [55]. A number of deliberate attempts have been made to develop the self-monitoring system [56].…”
Section: Non-invasive Methodsmentioning
confidence: 99%
“…Several calibration algorithms have been developed and implemented for portable setup [57]. There has been several concious efforts towards the development of the self-monitoring system [58].…”
Section: Non-invasive Methodsmentioning
confidence: 99%
“…The second consideration excludes the analysis of mechanical implants such as artificial limbs and biomedical systems that are not intended for in vivo operation. The structure, features and approach of the data used in this section corresponds to a taxonomy defined in [1] and [2]. This taxonomy encompasses a series of attributes of microelectronic-based IMDs, organized under 8 different categories.…”
Section: Survey Scope and Methodologymentioning
confidence: 99%
“…Different research groups have presented systems that provide functions such as drug delivery, closed-loop stimulation, and optical stimulation to correct visual ailments. Furthermore, it has been observed that trends in IMD design have been gradually shifting from rigid application-specific designs to flexible general-purpose systems [1], [2]. With the aim to understand the evolution of IMDs in the context of electronics systems, a survey of academic journal publications was made.…”
Section: Introductionmentioning
confidence: 99%